2013
DOI: 10.5101/nbe.v5i3.p131-139
|View full text |Cite
|
Sign up to set email alerts
|

Advances of Upconversion Nanoparticles for Molecular Imaging

Abstract: Molecular imaging is developing fast towards multi-modality and simultaneous therapy. For molecular imaging, upconversion nanoparticles (UCNPs), especially lanthanide-doped nanocrystals own obvious advantages such as low toxicity, large Stokes shifts, high resistance to photo-bleaching and photochemical degradation. Moreover, near infrared (NIR) excitation contributes to the auto-fluorescence minimization, a larger penetrating depth, and less harmfulness to cells compared with traditional ultraviolet (UV) exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…This can be understood from the growth mechanism. As is known to all that the formation of a particle includes initial production, subsequent growth, and final stabilization of nuclei [ 4 ]. Particle size is mainly determined by nucleation rate and a higher nucleation rate leads to a smaller particle size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be understood from the growth mechanism. As is known to all that the formation of a particle includes initial production, subsequent growth, and final stabilization of nuclei [ 4 ]. Particle size is mainly determined by nucleation rate and a higher nucleation rate leads to a smaller particle size.…”
Section: Resultsmentioning
confidence: 99%
“…It is probably because the β-NaREF 4 UCNPs provide over an order of magnitude stronger fluorescence than its corresponding cubic form [ 6 ]. On the other hand, owing to the larger surface quenching sites, smaller nanocrystals may suppress UC luminescence by enhanced nonradiative energy transfer processes of the luminescent lanthanide ions [ 4 ]. Compared to those tiny particles, the rod-like products have a relatively larger size and smaller ratio surface, leading to less surface defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We hoped to find early gastric cancer cells in vivo by multi-mode targeting imaging and serum biomarker detection techniques [ 7 - 12 ]. Our previous studies showed that subcutaneous and in situ gastric cancer tissues with 5 mm in diameter could be recognized and treated by using multi-functional nanoprobes such as BRCAA1-conjugated fluorescent magnetic nanoparticles [ 13 ], her2 antibody-conjugated RNase-A-associated CdTe quantum dots [ 14 ], folic acid-conjugated upper conversion nanoparticles [ 15 , 16 ], RGD-conjugated gold nanorods [ 17 ], ce6-conjugated carbon dots [ 18 ], ce6-conjugated Au nanoclusters (Au NCs) [ 19 , 20 ]. However, the clinical translation of these prepared nanoprobes still exists as a great challenge because no one kind of biomarker is specific for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3−7 In many cases, this new generation of luminescent nanoparticles forms the nuclei of multifunctional nanoplatforms where two or more of the functions described above can be carried out (either sequentially or simultaneously) in one nanoscale platform. 8,9 Traditionally, many of these luminescent nanoparticles studied have been optically excited following a conventional route whereby ultraviolet (UV) or visible light emissions are observed following excitation with higher energy photons. This can lead to various complications since often biological samples have inherent chromophores or fluorophores that could emit light when excited with high-energy radiation.…”
mentioning
confidence: 99%